2007
DOI: 10.1093/jpepsy/jsm102
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Napping Patterns in 3-to-5-year old Children Attending Full-Day Childcare Centers

Abstract: Findings indicate that the majority of 3-to-5-year-old children nap when given an opportunity. Preschool children's sleep and napping patterns on weekends and in other types of childcare environments warrant further research to assess health effects and impact on growth and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
59
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 17 publications
11
59
1
Order By: Relevance
“…Alternatively, children may unintentionally fall asleep in front of the television. Although children have a reduced need for naps as they mature, research has found that youngsters will fall asleep mid-day if placed in situations that are conducive to sleep (e.g., mandatory rest periods at daycare centers; Ward, Gay, Anders, Alkon, & Lee, 2007). The sedentary nature of television watching may therefore encourage napping even if it is not needed.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, children may unintentionally fall asleep in front of the television. Although children have a reduced need for naps as they mature, research has found that youngsters will fall asleep mid-day if placed in situations that are conducive to sleep (e.g., mandatory rest periods at daycare centers; Ward, Gay, Anders, Alkon, & Lee, 2007). The sedentary nature of television watching may therefore encourage napping even if it is not needed.…”
Section: Discussionmentioning
confidence: 99%
“…Both Ward et al [10] and Weissbluth [5] concluded that the majority of young children nap when given the opportunity: perhaps the availability or lack of opportunity to nap explains some of the variability in napping between children. Issues related to the provision of napping opportunities are the locations where naps take place, and the frequency of napping within children.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike nursery schools in countries such as the US [10] and Japan [11], most nursery schools in the UK do not provide children with the opportunity to nap. English children's opportunities to nap and napping patterns may therefore differ from those of children living elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…40 There is some evidence that daytime naps do not substitute for nighttime sleep in the prevention of obesity, 20 and that children who nap during child care may sleep fewer hours at night. 41 This may be especially important for parents whose children sleep for long durations during the day in child care. Future studies should explore the extent to which daytime naps contribute to the prevention of obesity when considering total daily sleep duration, as this information will have important implications for recommendations related to sleep in child care.…”
Section: Overviewmentioning
confidence: 99%
“…Previous studies have found that child care attendance was associated with shorter nighttime sleep duration for infants, 24 and that daytime sleep in child care decreased nighttime sleep at home for preschoolers. 41 Future sleep recommendations targeting child care settings should consider the relationship between parents and providers, as well as the extent to which daytime naps affect nighttime sleep duration.…”
Section: Overviewmentioning
confidence: 99%